Financial Opening under the WTO Agreement in Selected Asian Countries: Progress and Issues - Yun-Hwan Kim (Asian Development Bank (ADB), 2002)
"Opening of financial services has enormous policy implications for a member country. As demonstrated by the 1997 Asian crisis, mismanagement of financial opening may lead to disastrous economic consequences. Only prudent financial policies, including implementation of commitments under the General Agreement on Trade in Services, can result in macroeconomic stability, sustained output growth, and financial sector development. This paper examines six selected countries, i.e., People's Republic of China (PRC), Indonesia, Republic of Korea (Korea), Malaysia, Singapore, and Thailand. For the PRC, successful liberalization of financial services trade is of great importance. For the five other countries, all crisis-affected, there is a need to review ongoing financial liberalization policies and explore future directions. The paper examines the relationship between financial services liberalization and capital account liberalization, GATS and/or multilateral commitments made by the countries, progress in compliance of the commitments and their impact, and implications and issues of financial opening with focus on the banking sector. The paper suggests three guiding principles in opening financial services: (i) resource mobilization for economic recovery and sustained development, (ii) financial stability, and (iii) market competition."
hdl:11540/1966
Keywords: 330; WTO-Recht; GATS; Finanzdienstleistung; Finanzsektor; Kapitalbilanz; Deregulierung; Asien